NETWORK TRAFFIC ANALYSIS TOOLS - Boranbayev , S.; Kuanyshev , D. (EurasianUnionScientists, 2021)
The article studies network traffic analysis tools. Various aspects of network traffic analysis are considered algorithms and approaches to network traffic analysis, as well as software and hardware tools for effectively solving this problem. The article studies the current state of this area. It is given recommendations on what to pay attention when using network traffic analysis tools.